2017
DOI: 10.3390/ijerph14070793
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study to Determine the Prevalence of Hepatitis B and C Virus Infection in High Risk Groups in the Northeast Region of Brazil

Abstract: Background: HBV (Hepatitis B Virus) and HCV (Hepatitis C Virus) infections are more prevalent in vulnerable populations than the general population. The objective of this study was to investigate the prevalence of HBV and HCV infection in HIV-positive patients (GI), chronic renal failure (CRF) patients (GII) and coagulation disorder individuals (GIII). Methods: A cross-sectional study was conducted from June 2014 to March 2015. Serum samples were tested for markers of hepatitis B and C by enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
1
10
0
3
Order By: Relevance
“…In this study, HCV RNA was detected in 5.3% of the patients and genotype 1 was the most frequent, followed by genotypes 2 and 3 [74]. Recently, Barbosa-Ribeiro et al [17] found 12.6% of anti-HCV prevalence in Hemodialysis patients at Northeast Brazil. In Southeast region, anti-HCV prevalence of 13 and 14.8% was found in 2008 and 2010 years [75,76].…”
Section: Hepatitis B and C Prevalence In Patients With Chronic Kidneysupporting
confidence: 52%
See 4 more Smart Citations
“…In this study, HCV RNA was detected in 5.3% of the patients and genotype 1 was the most frequent, followed by genotypes 2 and 3 [74]. Recently, Barbosa-Ribeiro et al [17] found 12.6% of anti-HCV prevalence in Hemodialysis patients at Northeast Brazil. In Southeast region, anti-HCV prevalence of 13 and 14.8% was found in 2008 and 2010 years [75,76].…”
Section: Hepatitis B and C Prevalence In Patients With Chronic Kidneysupporting
confidence: 52%
“…As the same was found for HBV, Ferreira et al [98] observed a decrease in anti-HCV prevalence from 24.2% in 2007 to 4.7% in 2012. However, recent study in coagulopathy patients from Northeast Brazil found 47% of anti-HCV prevalence [17].…”
Section: Hbv and Hcv Infection Among Coagulopathy Patientsmentioning
confidence: 94%
See 3 more Smart Citations